Fine Mapping of CsVYL, Conferring Virescent Leaf Through the Regulation of Chloroplast Development in Cucumber - Song, Mengfei; Wei, Qingzhen; Wang, Jing; Fu, Wenyuan; Qin, Xiaodong; Lu, Xiumei; Cheng, Feng; Yang, Kang; Zhang, Lu; Yu, Xiaqing; Li, Ji; Chen, Jinfeng; et al. (Frontiers in Plant Science, 2018)
Leaf color mutants in higher plants are ideal materials for investigating the structure and function of photosynthetic system. In this study, we identified a cucumber vyl (virescent-yellow leaf) mutant in the mutant library, which exhibited reduced pigment contents and delayed chloroplast development process. F2 and BC1 populations were constructed from the cross between vyl mutant and cucumber inbred line ‘Hazerd’ to identify that the vyl trait is controlled by a simply recessive gene designated as CsVYL. The CsVYL gene was mapped to a 3.8 cM interval on chromosome 4 using these 80 F2 individuals and BSA (bulked segregation analysis) approach. Fine genetic map was conducted with 1542 F2 plants and narrowed down the vyl locus to an 86.3 kb genomic region, which contains a total of 11 genes. Sequence alignment between the wild type (WT) and vyl only identified one single nucleotide mutation (C→T) in the first exon of gene Csa4G637110, which encodes a DnaJ-like zinc finger protein. Gene Expression analysis confirmed the differences in transcription level of Csa4G637110 between wild type and mutant plants. Map-based cloning of the CsVYL gene could accelerate the study of chloroplast development and chlorophyll synthesis of cucumber.